Material Adverse Change Clauses and Acquisition Dynamics - Denis, David J.; Macias, Antonio J. (Journal of Financial and Quantitative Analysis, 2013)
Abstract Material adverse change (MAC) clauses are a ubiquitous feature of acquisitions and exhibit substantial cross-sectional variation in the number and types of events that are excluded from being material adverse events (MAEs). MAEs are the underlying cause of 69% ofacquisition terminations and 80% of renegotiations. These renegotiations lead to substantial changes in the price offered to target shareholders. Acquisitions with fewer MAE exclusions are characterized by wider arbitrage spreads during the acquisition period and are associated with higher offer premiums. We conclude that MAC clauses have an economically important impact on the dynamics of corporate acquisitions.